GROWTH AND SURVIVAL RATE OF AFRICAN CATFISH (Clarias gariepinus)USING BIOFLOCS TECHNOLOGY BY ADMINISTERING DIFFERENT DOSES OF PROBIOTIC BACTERIA (Bacillus) IN THE WATER MEDIUM OF PEAT BOG - Muhamad Latiful Khobir; Iskandar Putra; Usman M Tang (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted from December2015 until January 2016 at Technology Research and Development Center in Riau Balitbang.Thepurpose of this research was to investigate growth and survival rate of african catfish with addition bacterial dose in bioflocs techniques. This research using experimental method and completely random design (RAL) with three treatment and two replications, fourare P1 : 10 mL/m3 bacterial dose, P2 : 15 mL/m3bacterial dose, P3 : 20mL/m3bacterial dose. The result showed that african catfish with addition bacterial dose in bioflocs techniques affect significantly on the growth of absolute weight,the specific growth,but does not affect absolute length growth and survival rate. The best treatment were obtained in treatment P2 with 15mL/m3 bacterial dose, with value growth of absolute weight 50,15g, growth in absolute length 13,97cm, specific growth rate 3,39% and survival rate 98,16 %.   Keyword : african catfish, Dose bacteria, Bioflocs technology